Substituição da virginiamicina por produtos à base de levedura (Saccharomyces cerevisiae) em dietas de bovinos - Oliveira, Daiana dos Santos de (2020)
With the intensification of production systems, additives such as antibiotics have been widely used in the animals' diet in order to manipulate the rumen environment, avoiding metabolic disorders and improving the digestive efficiency of nutrients. However, some antibiotics have in their composition substances also present in medicines for human use, which can make treatments less effective due to the resistance of certain microorganisms, in addition to the high potential to pollute the environment, and can be banned from the diet provided to animals. In order to replace the use of antibiotics in the diet of cattle, this study used yeast-based products that are considered natural products and have a lower acquisition cost when compared to some antibiotics. The viability of this substitution was evaluated through the digestibility of nutrients and ruminal parameters. Five steers with dairy aptitude were distributed in a 5x5 Latin square. The diets contained roughage: concentrate ratio of 35.5: 64.5, with corn silage being the roughage used, and the concentrate was composed of ground corn, soybean meal, soybean husk, mineral core, calcitic limestone, urea and common salt. . The treatments were: VM: 18mg / kg in the material (MS) of Virginiamycin (VM); CL7: 7g of yeast culture; CL14: 14g of yeast culture; LA7: 7g of autolysed yeast; LA14: 14g of autolyzed yeast. No significant difference was found (P> 0.05) for dry matter consumption with: 8.22; 8.45; 8.33; 8.51 and 8.27 kg consumed; the dry matter digestibility was 61.41%; 53.79%; 57.46%; 54.45% and 55.83%, average ruminal pH of 6.75; 6.76; 6.76; 6.78 and 6.69, for VM; CL7; CL14; LA7 and LA14, respectively. Likewise, no significant difference was found for short-chain fatty acids and ammoniacal nitrogen between treatments, thus suggesting the possibility of replacing Virginiamycin with yeast-based products.